ANALISIS pH, C-ORGANIK, N-TOTAL DAN RASIO C/N TANAH LAHAN PERKEBUNAN KELAPA SAWIT DI DESA LOGAS KABUPATEN KUANTAN SINGINGI - Nopsagiarti, Tri; Anugrah Saputri, Monika; Putri Refiani, Tiara (Fakultas Pertanian, Program Studi Agroteknologi, 2025)
Oil palm is one of the plantation crops that is the main choice of farmers in Indonesia today. Land fertility is the main factor that determines the production of oil palm plants. The purpose of this study was to determine soil pH, C-organic content, N-total, and soil C/N ratio in smallholder oil palm plantations in Logas village, Kecamatan Singingi, Kabupaten Kuantan Singingi. The research was conducted using a survey method, taking soil samples by purposive sampling on oil palm land aged 3, 5, and 7 years. The results showed that the soil in oil palm plantations in Logas village had a pH of 6.05-6.55 with acidic to slightly acidic criteria, C-organic content in the range of 0.56-1.16 with very low to low criteria, N-total ranging from 0.05 to 0.11 with very low to low criteria, and a C/N ratio with low-medium criteria.